Value-centric design architecture based on analysis of space system characteristics. (March 2018) - Xu, Q.; Hollingsworth, P.; Smith, K.
Abstract: Emerging design concepts such as miniaturisation, modularity, and standardisation, have contributed to the rapid development of small and inexpensive platforms, particularly cubesats. This has been stimulating an upcoming revolution in space design and development, leading satellites into the era of "smaller, faster, and cheaper". However, the current requirement-centric design philosophy, focused on bespoke monolithic systems, along with the associated development and production process does not inherently fit with the innovative modular, standardised, and mass-produced technologies. This paper presents a new categorisation, characterisation, and value-centric design architecture to address this need for both traditional and novel system designs. Based on the categorisation of system configurations, a characterisation of space systems, comprised of duplication, fractionation, and derivation, is proposed to capture the overall system configuration characteristics and promote potential hybrid designs. Complying with the definitions of the system characterisation, mathematical mapping relations between the system characterisation and the system properties are described to establish the mathematical foundation of the proposed value-centric design methodology. To illustrate the methodology, subsystem reliability relationships are therefore analysed to explore potential system configurations in the design space. The results of the applications of system characteristic analysis clearly show that the effects of different configuration characteristics on the system properties can be effectively analysed and evaluated, enabling the optimization of system configurations. Highlights: System characteristic space is proposed to capture configuration characteristics. A categorisation and characterisation of several example systems is presented. A value-centric design method using the system characteristic space is presented. The mapping relationship between system designs and characteristics is developed. Effects of system characteristics are analysed to explore the design space.